Implementing Implicit Schemes in GENSMAC - Oishi, C.M.; Ferreira, V.G.; Cuminato, J.A.; Castelo, A.; Tomé, M.F.; Mangiavacchi, N. (Trends in Computational and Applied Mathematics, 2004)
Implicit schemes are studied with the purpose of introducing them in the two-dimensional GENSMAC method, for the numerical solution of unsteady newtonian incompressible flows. By using the fractional-step approach, the Freeflow2D simulation system is employed to solve the conservation equations. The viscous terms in the Navier-Stokes equations are implicitly treated via the Implicit Backward (IR), Crank-Nicolson (CN) and Adams-Bashforth/Crank-Nicolson (AB/CN) schemes. The convective terms are explicitly treated by the upwind differencing Variable Order Non-Oscillatory Scheme (VONOS) scheme. For channel and impinging jet flows, the numerical techniques are robust and produce results that compare very well with the analytical solutions.